Somatotype of the best ranked Croatian superleague female volleyball players: differences between playing roles - Rešetar, T.; Marinovic M.; Ambrus, P. (Croatian Sports Medicine Journal, 2020)
The aim of this research is to determine significant differences in somatotype of playing roles among Croatian female volleyball players who compete in the highestranking national competition. The sample of examinees was constituted out of female volleyball players (n=52) from four top-seeded teams that competed in the Croatian Superliga in the 2018/2019 season. The players` somatotype was assessed based on ten anthropometric measurements for the following playing roles: setter, libero, opposite, receiver and centre. The significance of the differences between the playing roles in anthropometric indicators and somatotype components was determined by using the univariate analysis of variance (ANOVA), whereas the difference between pairs of individual playing roles was established by a series of post hoc Tukey tests. Significant differences were found between playing roles in the variables body height, body weight, humerus breadth diameter, mesomorphs and ectomorphs. It was determined that opposites and centres are taller than receivers, setters and liberos, whereas receivers are taller than liberos. Regarding to body weight, opposites are heavier than setters, liberos and receivers. According to humerus breadth diameter, opposites showed higher values than liberos and setters. In view of individual components of somatotype, liberos have a significantly higher mesomorph component than centres, while centres have a significantly higher ectomorph component than all other playing roles. The average somatotype of all the female volleyball players is endomorphic ectomorph (3.1-2.4-3.6). Setters and receivers belong to the endomorph-ectomorph category (3.0-2.7-3.3, 3.3-2.7-3.5). Liberos pertain to the mesomorph-endomorph category (3.1-3.3 2.7). Opposites fall into the endomorph-ectomorph category (3.4-1.9-3.6), whereas centres are in the endomorphic ectomorph category (3.0-1.6-4.5). The somatotype of some of the elite female Croatian Superliga volleyball players was determined for the first time in this research, which thus expands the global database of anthropometric characteristics for female volleyball players, as well as simultaneously provides valuable data for production and implementation of future training programs and a higher level of quality in the selection of playing roles in Croatia.